Pengaruh Literasi Keuangan, Uang Saku, Pendidikan Keuangan Di Keluarga Dan Lifestyle Hedonis Terhadap Perilaku Keuangan Mahasiswa - Ajeng Trixsiana; Wiwik Lestari (Universitas Dr. Soetomo, 2024)
This research aims to examine the influence of financial literacy, pocket money, financial education in the family and hedonic lifestyle on students' financial behavior. The sample consisted of 240 respondents with the characteristics of active students from economics and business faculties at Surabaya universities, students who still received pocket money. Sampling in this research used non-probability sampling and purposive sampling methods. Analysis uses Structural Equating Modeling (SEM) on Partial Least Square (PLS) and data collection uses a survey method using a questionnaire. The results of this study show that financial literacy is not significant on financial behavior, pocket money has a significant positive effect on financial behavior, financial education in the family has a significant positive effect on financial behavior, hedonic lifestyle has a significant negative effect on financial behavior.